Autoantibodies of patients with coeliac disease are insufficient to block tissue transglutaminase activity. Issue 11 (21st October 2003) - Dieterich, W; Trapp, D; Esslinger, B; Leidenberger, M; Piper, J; Hahn, E; Schuppan, D
Abstract : Background and aims: Coeliac disease (CD) is characterised by the presence of autoantibodies against tissue transglutaminase (tTG), the endomysial autoantigen. This study was performed to determine the effect of purified autoantibodies on the enzymatic activity of tTG. Methods: Total IgA and IgG class antibodies and purified anti-tTG autoantibodies were isolated from sera of untreated patients with CD and controls. The inhibitory capacity of the antibodies on tTG activity was checked by a fluorometric assay based on the incorporation of monodansyl cadaverine into casein and by tTG-catalysed cross linking of biotinylated cadaverine to gliadin. Results: The enriched IgA and IgG fractions of five patients with CD and three controls resulted in no significantly different inhibition of enzymatic activity. In contrast, the use of affinity purified anti-tTG autoantibodies of 12 patients with CD led to a dose dependent reduction of tTG activity, compared to control immunoglobulins (n=6). However, the remaining activity was sufficient for cross linking of cadaverine into gliadin, and enzymatic tTG activity was only blocked completely by high concentrations of a monoclonal antibody, which is directed to the active centre of tTG. Conclusions: Despite a partial inhibitory effect of isolated anti-tTG autoantibodies from patients with CD, residual enzymatic activity remains sufficiently high to cast doubt on their in vivo relevance.